Kebijakan berorientasi ganda pada industri kelapa sawit: Antara visi kerakyatan dan efisiensi - Priyonggo Suseno (Universitas Islam Indonesia, 1999)
Crude Palm Oil industry is one of the mature industrial sectors in Indonesia. This industry has been growing since 1939. Unfortunately, this industry still could not grow steadily although government has give incentives to this industry/ The profitable exchange rate (FOB price) of CPO could not raise the export volume.